Simon Polotsky and his child-rearing beliefs - Zvonareva Л.У.; Zvonarev О.В. (Bulletin of the L.N. Gumilyov Eurasian National University. Political Science. Regional Studies. Oriental Studies. Turkology Series., 2018)
The authors analyze Simon Polotsky’s credo evolution in child-rearing beliefs. The authors suppose his credo to represent a kind of Hellenic cultural traditions and Christian ideas synthesis being influenced by moods and spirits prevailed in the Kiev-Moguilyansk college he had graduated from. The brief analysis of the one of the outstanding Cristian enlighteners heritage enables the authors to believe Simon Polotsky to have popularized in his creative activities progressive Pedagogical theories, as well as book printing experience derived during his studies at the above-menioned college.